Anatomical characterization of vegetative organs and scapes of Rondonanthus (Eriocaulaceae, Poales) - de Oliveira, Fernanda Martins Gonzaga [UNESP]; Oriani, Aline [UNESP] (Springer Nature, 2016)
Eriocaulaceae is a pantropical family and comprises ten genera. Rondonanthus is endemic to the north region of South America and comprises six species. The anatomy of roots, stem, leaves, and scapes were studied in four species to characterize the genus and to identify characteristics with taxonomic value. The following characteristics are diagnostic of Rondonanthus: roots—heterogeneous cortex with an aerenchyma supported by arm cells and vascular cylinder with a central metaxylem vessel element; stems—idioblasts with druses in the cortex and in the pith; leaves—Malpighian hairs, hypodermis in the adaxial surface, chlorenchyma with arm cells, druse idioblasts in the mesophyll, and vascular bundle sheath extensions with rounded cells; scapes—Malpighian hairs and chlorenchyma with arm cells. Rondonanthus capillaceus differed from the remaining studied species by presenting roots with a homogeneous cortex with thin-walled cells; filiform leaves without stomata and trichomes but with a chlorophyllous epidermis and a parenchymatous mesophyll and only one central vascular bundle without sheath extension. Such differences may be related to the habitat, since this species grows on river margins and requires hydrodynamic organs. The number of vascular bundles in the leaves is a useful characteristic to differentiate among species.
Keywords: Anatomy; Leaf; Reproductive axis; Root; Stem